2021
DOI: 10.1002/smll.202102938
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Sugar‐Based Chiral and Flower‐Like Microparticles

Abstract: Unique supermolecular structures as chiral and flower‐like microparticles and the precise tuning of the morphologies hold immense promise for a variety of applications. Examples of such structures deriving from monosaccharides are still rare, and a general understanding is also lacking. Herein, it is shown that chiral, flower‐like, or solid microparticles can be tuned by only using monosaccharide esters without external stimuli. Chiral “left‐handed” (counterclockwise) and “right‐handed” (clockwise) morphologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The stearoyl esters have been introduced on different monosaccharides and their enantiomer under mild conditions. [ 23 ] In another study, six synthetic oligosaccharides ranging from dimers to hexamers carrying benzyl ethers, methylated analogue or acetylated analogue can self‐assemble into nanostructures of varying morphologies, such as vesicles and fibers ( Figure a). [ 37 ] The introduced groups helped with the encountered poor solubility and low reactivity issues.…”
Section: Design Of the Carbohydrate‐based Building Blocks In Self‐ass...mentioning
confidence: 99%
See 4 more Smart Citations
“…The stearoyl esters have been introduced on different monosaccharides and their enantiomer under mild conditions. [ 23 ] In another study, six synthetic oligosaccharides ranging from dimers to hexamers carrying benzyl ethers, methylated analogue or acetylated analogue can self‐assemble into nanostructures of varying morphologies, such as vesicles and fibers ( Figure a). [ 37 ] The introduced groups helped with the encountered poor solubility and low reactivity issues.…”
Section: Design Of the Carbohydrate‐based Building Blocks In Self‐ass...mentioning
confidence: 99%
“…Yao et al reported the formation of chiral microparticles by using monosaccharide stearoyl esters (MSSEs) without using external stimuli. [23] Four types of MSSEs including glucose stearoyl ester (GlcSE), xylose stearoyl ester (XylSE), galactose stearoyl ester (GalSE), and mannose stearoyl ester (ManSE) were compared. It was shown that only GlcSE with a certain α/β ratio (GlcSE20/80) can form chiral microparticles (Figure 4a-c).…”
Section: Internal Factorsmentioning
confidence: 99%
See 3 more Smart Citations